The effectiveness of (the Baby Building Model) in the achievement of fifth year middle school students In the course of drawing engineering perspective (Journal of the College of Basic Education, 2022)
The current research aims to develop the skills of fifth-year iddle school students in the subject of drawing the engineering perspective. To study this, the researcher identified building instructional plans for the skills of drawing an engineering perspective according to the Babi constructive model.And two null hypotheses were formulated:-There are no statistically significant differences at the level of significance (0.05) between the grades of the grades of the two groups (experimental and control) in assessing the skill performance prior to.- There are no statistically significant differences at the level of significance (0.05) between the grades of the grades of the two groups (experimental and control) in assessing the skill performance dimensional. The results of this research showed the following:The effectiveness of teaching plans according to (Babi constructive model) in developing the skills of drawing the engineering perspective for the fifth preparatory students - the experimental group. Which had a positive effect to get the desired results